An empirical study of leadership style and procedural justice and organizational citizenship behavior into a driver of improving employee performance - Dadan Faturohman; Fauji Sanusi; Roni Kambara (Jurnal Mantik, 2023)
This study aims to test and analyze the factors that can improve employee performance at the Pandeglang Regency Education, Youth, and Sports Office, namely the variables of leadership style, procedural justice, and organizational citizenship behavior that have been modeled by the author so that it will be tested for validity. This research was conducted at the Office of Education, Youth and Sports of Pandeglang Regency. This research uses quantitative methods by using causality, namely looking for explanations in the form of cause-and-effect relationships between several variables; the sampling technique used in this study is saturated sampling or total sampling, where all populations are sampled, namely, all employees of the Pandeglang Regency Disdikpora totaling 150 respondents and data analysis techniques with Partial Least Square (PLS) software. The results showed that leadership style positively and significantly affected employee performance. Procedural justice has a positive and significant impact on employee performance. Leadership style has a positive and significant impact on organizational citizenship behavior. Procedural justice has a positive and significant effect on organizational citizenship behavior. Organizational citizenship behavior has a positive and significant effect on employee performance. Organizational can be characterized as partial mediation on the effect of leadership style on employee performance and the effect of procedural justice on employee performance. In this context, the author hopes that this research is expected to make a theoretical contribution to the literature on human resource management.